Effect of fluid presence on the nonaxisymmetric dynamic response of buried orthotropic cylindrical shells under a moving load - Singh V.P.; Dwivedi J.P.; Upadhyay P.C. (My University, 2025)
This paper deals with the nonaxisymmetric dynamic behavior of fluid-filled buried orthotropic cylindrical shells/pipes subjected to a load moving along the axis of the shell. A thick shell model including the effects of shear deformation and rotary inertia is considered. A perfect bond between the shell and surrounding soil is assumed. The linear acoustic equation is used for the wave propagation in the fluid inside the pipe. Results are presented for the axisymmetric as well as the flexural mode for different orthotropy parameters of the shell and for different soil conditions around the pipe. Results of empty and fluid-filled shells are compared. The presence of fluid inside the shell has small effect on the shell response. However, the deformations in the fluid-filled shell are normally more than those in the empty shell. The difference in the displacements of empty and fluid-filled shells is very small in flexural mode as compared to axisymmetric mode. The effect of fluid presence on the shell response is also influenced by the nature of the surrounding soil. © 2000 Sage Publications, Inc.